1998
DOI: 10.1007/s11745-998-0254-2
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic acid does not affect aggression of normal volunteers under nonstressful conditions. A randomized, placebo‐controlled, double‐blind study

Abstract: We previously found that docosahexaenoic acid (DHA) intake prevents aggression enhancement at times of mental stress. In the present study we investigated changes in aggression under nonstressful conditions. Forty-six students of two universities took either DHA-rich fish oil capsules containing 1.5 g DHA (DHA group: 13 males and 9 females) or control oil capsules containing 97% soybean oil plus 3% of another fish oil (control group: 11 males and 13 females) for 3 mon in a double-blind fashion. At the start an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 21 publications
3
21
0
1
Order By: Relevance
“…Few studies have investigated the effects of n-3 supplements on hostility or aggression. In one study, DHA supplementation with oil capsules prevented an increase in aggression at times of stress among Japanese students (Hamazaki et al, 1996) but had no effect in non-stressful situations (Hamazaki et al, 1998). Similar findings by the same authors were reported in an elderly cohort of white-collar workers but not in rural villagers (Hamazaki et al, 2002).…”
Section: Discussionsupporting
confidence: 58%
“…Few studies have investigated the effects of n-3 supplements on hostility or aggression. In one study, DHA supplementation with oil capsules prevented an increase in aggression at times of stress among Japanese students (Hamazaki et al, 1996) but had no effect in non-stressful situations (Hamazaki et al, 1998). Similar findings by the same authors were reported in an elderly cohort of white-collar workers but not in rural villagers (Hamazaki et al, 2002).…”
Section: Discussionsupporting
confidence: 58%
“…Other studies have reported EPA plus DHA levels expressed as percent of total fatty acids as 3.81% [38] and 5.57% [39].…”
Section: Discussionmentioning
confidence: 99%
“…This same dose appeared to decrease the level of norepinephrine (NE), but not other catecholamines, in medical students during exams [262]. Interestingly, when aggression was determined during a non-stressful time, there was no change in aggression in the DHA group and a slight decrease in the control group [263]. It is possible DHA supplementation is offering protection during stressful conditions.…”
Section: Other Disordersmentioning
confidence: 99%